2017
DOI: 10.1101/138958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A combined use of intravoxel incoherent motion MRI parameters can differentiate early stage hepatitis-b fibrotic livers from healthy livers

Abstract: This study investigated a combined use of IVIM parameters Dslow (D), PF (f) and Dfast (D*) for liver fibrosis evaluation. 16 healthy volunteers (F0) and 33 hepatitis-b patients (stage F1= 15, stage F2-4 = 18) were included. With a 1.5-T MR scanner and respiration-gating, IVIM diffusion weighted imaging was acquired using a single-shot echo-planar imaging sequence with ten b-values of 10, 20, 40, 60, 80, 100, 150, 200, 400, and 800 s/mm2. Signal measurement was performed on right liver parenchyma. With a 3-dime… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
31
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(41 citation statements)
references
References 61 publications
(108 reference statements)
9
31
1
Order By: Relevance
“…This highlights the limitation of accurate D' Vfast value estimation. Interestingly, in a previous study where the lowest b-value was b = 10 s/mm 2 , reducing the tri-exponential to a bi-exponential model, 17 the D fast value was 12.34 ± 3.06 × 10 −3 mm 2 /s, thus close to our D' fast value (≈15 × 10 −3 mm 2 /s).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This highlights the limitation of accurate D' Vfast value estimation. Interestingly, in a previous study where the lowest b-value was b = 10 s/mm 2 , reducing the tri-exponential to a bi-exponential model, 17 the D fast value was 12.34 ± 3.06 × 10 −3 mm 2 /s, thus close to our D' fast value (≈15 × 10 −3 mm 2 /s).…”
Section: Discussionsupporting
confidence: 85%
“…Note that adjusted R 2 is a better indicator when comparing nested models, since its calculation takes into account the number of parameters (References and Supplementary Document 2). Using ROI analysis, an R 2 value higher than 0.95 generally indicates good fit …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wáng and colleagues provided a particularly interesting work on application of IVIM diffusion imaging for the diagnosis of hepatic fibrosis without steatosis (8). The methodology used is original.…”
mentioning
confidence: 99%
“…Wang et al [1, 5], Huang et al [2], and Li et al [6] recently demonstrated that Diffusion MRI derived IVIM measurements can offer high performance in detecting liver fibrosis. However, the disadvantages of IVIM measurement include long scan time to acquire multiple b -value imaging data, and this itself is often associated with respiration induced motion artefacts.…”
Section: Discussionmentioning
confidence: 99%